Queen's Park Hotel; Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad, 2010)
This postcard shows a front view of the renovated Queen's Park Hotel, located south of the Queen's Park Savannah. Originally built in 1893. This reconstruction completed in 1937 saw the centrepiece of the original hotel being demolished for a modern Art Deco structure with five floors. There are several taxis parked outside the building. Postcard number J435.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Hotels--Trinidad and Tobago; [1950]; Buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Transportation--Trinidad and Tobago; Taxicab industry--Trinidad and Tobago; Taxicabs--Trinidad and Tobago; Roads--Guard fences; Balconies--Trinidad and Tobago; Trees--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)